Implementasi QoS dengan Kombinasi Queue tree dan Dynamic Queue Untuk Meningkatkan Kualitas Jaringan (Kasus Balai Desa Sera, Kab. MBD) - Aitiameru, Hendra; Christianto, Erwien (STIKOM Tunas Bangsa Pematangsiantar, 2024)
This study delves into the implementation of Quality of Service (QoS) through the synergistic integration of Queue tree and Dynamic Queue mechanisms aimed at enhancing network quality. QoS plays a pivotal role in ensuring optimal network performance by effectively managing and prioritizing various types of network traffic. The Queue tree method offers a hierarchical approach to traffic management, while the Dynamic Queue method enables adaptive allocation of network resources based on real-time network conditions. Through comprehensive implementation and testing within a simulated network environment, this research demonstrates the efficacy of combining Queue tree and Dynamic Queue techniques in bolstering network performance. The results underscore the significance of this integrated approach in providing tailored prioritization of diverse service types and dynamically adjusting resource allocation, thereby substantiating its viability as a solution for augmenting network quality.